“Keren” Kreasi Olahan Gula Aren di Sekolah - Astuti, Eny (Pena Edukasia, 2023)
The concept of entrepreneurial character according to the student profile strengthening program Pancasila seeks to build the ability of students to hone the soul entrepreneurship from an early age, teaches honesty, creativity, cooperation, responsibility and never give up. The character of this Pancasila student becomes part of efforts to build global competence of Indonesian students as lifelong learners with behavior according to Pancasila values ??in the midst of the era of society 5.0. Hopefully, with entrepreneurial ability with character, students are able to seize opportunities and compete locally, regionally and globally. The results of observations found in the field show that entrepreneurship education has not become an integrated part of the curriculum at SD Negeri Duren. Observation results of SD conditions Negeri Duren shows that there is a school environment that has a geographic location mountainous dacrabs with excellent agricultural potential are regions palm sugar producer Based on the background and development needs edupreneurship and the support of previous studies, processed sugar creations were developed aren't because of SD Negeri Duren. Edupreneurship Activity Center. This program can become a means of education, especially edu hortipreneurship in schools.